The effects of topical liposomal resveratrol on incisional and excisional wound healing process - Günal, Mehmet Yalçın; Ayla, Şule; Bedri, Nejda; Beker, Mustafa Çağlar; Çağlayan, Ahmet Burak; Aslan, İsmail; Özdemir, Ekrem Musa; Yeşilada, Erdem; Kılıç, Ülkan (Turkish Society of Dermatology and Venereology, 2019)
Background and Design: The objective of this study was to investigate the wound healing activity of different concentrations of liposomal trans-resveratrol formulations on incisional and excisional wounds in rats. Materials and Methods: The wound healing effect was tested by an excisional and incisional wound model. Wound closure was measured for 12 days. On the 12th day of the study, maximal load, maximum stress, stress, and % of elongation values were evaluated in the incisional wound. In addition, angiogenesis, granulation tissue thickness, epidermal and dermal regeneration values, and macroscopic photographic analyses were evaluated in the excisional wound. Results: When the wound tissue surface healing rates were evaluated, similar effects were observed at the end of the 10th and 12th days between the 5% Res group and the commercial product containing 1% Centella asiatica extract used as the reference molecule. Histological evaluation showed that 1% Res and 5% Res groups induced significant wound healing activity compared to the control group. Furthermore, 1% Res and 5% Res groups increased wound healing rates by promoting granulation tissue, epidermal, and dermal regeneration as well as angiogenesis. Conclusion: Liposomal formulations containing 1% and 5% resveratrol were found to have positive effects on the healing process, both on excisional and incisional wound tissues.

Amaç: Bu çalışmanın amacı, sıçanlarda insizyonel ve eksizyonel yaralar üzerine farklı konsantrasyonlarda hazırlanmış lipozomal trans-resveratrol formülasyonlarının yara iyileşme aktivitesi üzerine etkinliğini araştırmaktır. Gereç ve Yöntem: Yara iyileşme etkisi, eksizyonel ve insizyonel yara modeli kullanılarak test edildi. Yara yüzey alanları 12 gün süresince ölçüldü. Çalışmanın 12. gününde, insizyonel yaralarda maksimum yük, maksimum stres, gerginlik (strain) ve % uzama değerleri değerlendirildi. Ek olarak, eksizyonel yaralarda anjiyogenez, granülasyon dokusu kalınlığı, epidermal ve dermal rejenerasyon değerleri ve makroskopik fotoğraf analizleri değerlendirildi. Bulgular: Yara dokusu yüzey iyileşme oranları değerlendirildiğinde, %5 Res grubu ile referans molekül olarak kullanılan 1% Centella asiatica ekstresi arasında 10. ve 12. günlerde benzer etkiler gözlendi. Histolojik değerlendirme, %1 Res ve %5 Res gruplarının kontrol grubuna kıyasla anlamlı yara iyileşme aktivitesi oluşturduğunu gösterdi. Ayrıca, %1 Res ve %5 Res grupları, granülasyon dokusu, epidermal ve dermal rejenerasyonun yanı sıra anjiyogenezi uyararak yara iyileşme oranlarını arttırdı. Sonuç: %1 ve %5 resveratrol içeren lipozomal formülasyonların, hem eksizyonel hem de insizyonel yara dokularında iyileşme süreci üzerinde olumlu etkileri olduğu bulunmuştur.
Topikal lipozomal resveratrolün insizyonal ve eksizyonal yara iyileşme sürecine etkileri
Keywords: Resveratol; Liposome; Incisional Wound; Excisional Wound; Axial Tensile-Elongation Tests; Resveratol; Lipozom; Insizyonal Yara; Eksizyonal Yara; Eksenel Çekme-Uzama Testleri